Emulsification and pH Control for Sustainable Thermochemical Fluids Reactivity - Ali A. Al-Taq; Murtada Saleh Aljawad; Olalekan Saheed Alade; Hassan M. Ajwad; Sidqi A. Abu-Khamsin; Shirish Patil; Mohamed Mahmoud (Molecules)
Managing chemical reactivity is crucial for sustainable chemistry and industry, fostering efficiency, reducing chemical waste, saving energy, and protecting the environment. Emulsification is used for different purposes, among them controlling the reactivity of highly reactive chemicals. Thermochemical fluids (TCFs), such as NH4Cl and NaNO2 salts, have been utilized in various applications, including the oil and gas industry. However, the excessive reactivity of TCFs limits their applications and consequently negatively impacts the potential success rates. In this study, an emulsification technique was employed to control the high reactivity of TCFs explored at 50% and 70% in diesel, using three distinct emulsifier systems at concentrations of 1%, 3%, and 5% to form water-in-oil emulsions. The reactivity of 4M neat TCFs and emulsified solutions was examined in an autoclave reactor as a function of triggering temperatures of 65–95 °C, volume fraction, and emulsifier type and concentration. Additionally, this study explores an alternative method for controlling TCF reactivity through pH adjustment. It investigates the impact of TCFs at pH values ranging from 6 to 10 and the initial pressure on the resulting pressure, temperature, and time needed to initiate the TCF’s reaction. The results revealed that both emulsification and pH adjustment have the potential to promote sustainability by controlling the reactivity of TCF reactions. The findings from this study can be utilized to optimize various downhole applications of TCFs, enhancing the efficiency of TCF reactions and success rates. This paper presents in detail the results obtained, and discusses the potential contributions of the examined TCFs’ reactivity control techniques to sustainability.